Pelatihan Packaging Teh Herbal dari Bahan Alam Desa Namo Sialang Kabupaten Langkat Sumatera Utara - Julianti, Elisa; Irni, Julaili; Zuliyanti, Ameilia; Batubara, Ridwanti; Pinem, Laura Juita; Pratomo, Bayu (Jurnal Pengabdian UNDIKMA, 2024)
This community service program aims to increase the knowledge and skills of Women in Namo Sialang Village, packaging herbal tea products produced by processing natural ingredients like rose, tawar and sembur (made from special spices and herbs from the community). The method for implementing this service used participatory training with activities including socialization and assistance with product packaging. The number of participants involved was 20, consisting of a Women Group named "NandeTa". The evaluation instrument used in this activity was a questionnaire, which was analyzed descriptively. The results of the service showed that there had been an increase in the knowledge and skills of "NandeTa" in packaging the herbal tea that had been produced. Apart from that, "NandeTa" also became aware that packaging was one attraction that stimulates consumer buying interest, especially in tourist areas.